2020
DOI: 10.1017/s0021932019000853
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the prevalence of overweight/obesity and adiposity among pre-school children in Kraków, Poland, from 2008 to 2018

Abstract: Socioeconomic changes occurring over time influence the lifestyle choices of a population, and these can significantly affect children’s body weight and composition. The aim of this study was to assess the changes in prevalence of overweight, obesity and adiposity in pre-school children in Poland between 2008 and 2018. Body height, body weight and subscapular and triceps skinfolds were measured in 2167 children aged 3–7 years from Kraków. Body mass index and adiposity (percentage body fat, %BF) were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…Pooled results from all analyzed studies showed sensitivity of 73%, suggesting over a quarter of children not labelled as obese by BMI might indeed have excess adiposity [47]. Similar outcomes was found in study among Polish preschool children form Krakow City [48], which combined with present study outcomes could suggest that associations between excess adiposity and excess weight among Polish children stays in line with the findings form other high developed countries.…”
Section: Discussionsupporting
confidence: 89%
“…Pooled results from all analyzed studies showed sensitivity of 73%, suggesting over a quarter of children not labelled as obese by BMI might indeed have excess adiposity [47]. Similar outcomes was found in study among Polish preschool children form Krakow City [48], which combined with present study outcomes could suggest that associations between excess adiposity and excess weight among Polish children stays in line with the findings form other high developed countries.…”
Section: Discussionsupporting
confidence: 89%
“…What is producing these marked declines in the prevalence of high BMI, particularly across all groups examined, is uncertain. Others have suggested that contributions towards declines in overweight and obesity in preschool children could include: efforts to focus on public health interventions and initiatives (promoting healthy eating and physical activity) [ 25 , 29 , 30 ], increased parental education [ 29 , 33 ], decreasing unemployment rates [ 33 ], decreased maternal smoking during pregnancy [ 23 ], increased breastfeeding prevalence [ 23 ] and increasing proportion of mothers born overseas where lower population BMIs are present [ 35 ]. A recent analysis of New Zealand data suggests that continued reductions in maternal smoking during pregnancy may be at least playing a part in the decline found in our study [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, the prevalence of overweight/obesity among children and adolescents aged 5–19 years soared from 8.5% in 2010 to 19.0% in 2020 7. Data from other countries (such as Spain,8 China,9–12 Greece,13 Poland14 and Australia15) also showed the high prevalence of overweight and obesity among children and adolescents. Generally, obesity in childhood is a worldwide epidemic requiring urgent actions and practical interventions.…”
Section: Introductionmentioning
confidence: 94%